Bahasa Inggris - Umi Rahmawati; Surya Raharja (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study investigates the influence of herding behavior, loss aversion, and availability on investment decision-making among Generation Z, with Fear of Missing Out (FoMO) as a mediator. Generation Z frequently relies on social media as a primary source of investment information, potentially leading to biases or decision-making errors. The research was conducted among a group studying capital markets in Semarang, employing purposive sampling to gather data from 251 respondents through Google Form questionnaires. Data analysis using Smart PLS 4.0 revealed that herding behavior does not significantly affect FoMO or investment decision-making among Generation Z. However, loss aversion and information availability significantly influence both investment decision-making and FoMO among Generation Z. FoMO does not mediate the relationship between herding behavior and investment decisions, but it does mediate the impact of loss aversion and information availability on investment decisions among Generation Z.